A Whetstone of Wealden Sandstone from the Roman Villa at Great Holts Farm, Boreham, Essex. (14th July 2015) - Allen, J.R.L.
Abstract Excavated in 1992–4, the villa yielded a portion of a whetstone which, on the basis of general shape, the presence of rebated long edges and microscopic petrography in thin-section, was with little doubt made from a sandstone in the Weald Clay Formation (Lower Cretaceous) of the north-west Weald. It is representative of a widely recorded, major stone-based industry in Roman Britain, with finds known to range from the Channel coast to the northern frontier zone.